Evaluation of Communication Management on Project Success: A Case Study of the Construction of the PT. XYZ - Alvin Jayadinata Lukito; Ridho Bayuaji; Ervina Ahyudanari; Putu Dana Karningsih (Jurnal Indonesia Sosial Teknologi, 2024)
PT. XYZ is an agro-business company in Gresik, East Java, which is currently in the factory construction stage. Field obstacles often occur, so the process of conveying information from all stakeholders involved is important. The author will evaluate communication management factors that influence project success using EFA-Maximum Likelihood and Spearman's rank order correlation. This analysis identified nine important factors: information technology, communication technology, communication skills, communication management plan, teamwork, clear channels in the organizational structure, project requirements management, project risk management, and environmental context. The language acquisition factor was excluded because it did not meet the EFA requirements. Spearman's rank order correlation shows that information technology, communication skills, communication management plans, teamwork, clear channels, project requirements management, and environmental context have a strong relationship with project success. These findings guide improving project communication management to achieve project success.